2022
DOI: 10.1063/5.0123357
|View full text |Cite
|
Sign up to set email alerts
|

Display of converse and direct magnetoelectric effect in double perovskite LaYFe2O6

Abstract: This work reports the simultaneous observation of converse magnetoelectric (CME) and direct magnetoelectric (DME) effects in LaYFe2O6. The structural, magnetic, and magnetoelectric properties of LaYFe2O6, prepared by the sol-gel auto-combustion method and sintered at various temperatures, have been studied. The x-ray powder diffraction study suggests the double perovskite structure with symmetries P21nm (∼90%) and Pbnm (∼10%). The alternate ordering of La and Y ions is confirmed by the neutron powder diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The presence of diffraction peaks at ∼18.40°(orange arrow mark) and ∼20.16°(red arrow mark) validates the presence of a nonpolar alpha phase and a polar beta phase of PVDF, respectively. 25 In the composite films, all of the diffraction peaks of the filler NP 22 (shown in the inset of Figure 1b) are witnessed in the XRD pattern. So, the XRD pattern of the nanocomposites manifests the existence of both a magnetic NP and a piezoelectric polymer.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The presence of diffraction peaks at ∼18.40°(orange arrow mark) and ∼20.16°(red arrow mark) validates the presence of a nonpolar alpha phase and a polar beta phase of PVDF, respectively. 25 In the composite films, all of the diffraction peaks of the filler NP 22 (shown in the inset of Figure 1b) are witnessed in the XRD pattern. So, the XRD pattern of the nanocomposites manifests the existence of both a magnetic NP and a piezoelectric polymer.…”
Section: Resultsmentioning
confidence: 96%
“…The reduction of the ME coupling coefficient in the PS20 and PS30 compositions is ascribed to the enhanced conductivity compared to that of PS10 (see later discussions) and the gradual decrease of the beta phase of PVDF. For comparison, the plot of pristine LO is also displayed, and it exhibits a magnitude of 1 order lower than the film samples (∼0.45 mV cm –1 Oe –1 ) . The inset of Figure a displays the histogram plots of alpha d at 300 K. It is reported that the ME effect in LO strongly depends on the electrical resistivity and the ME coupling coefficient decreases with the temperature as the resistivity decreases .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations